Comparison of Gut Microbiota Between Golden and Brown Noble Scallop Chlamys nobilis and Its Association With Carotenoids - Liu, Hongxing; Tan, Kar Soon; Zhang, Xinxu; Zhang, Hongkuan; Cheng, Dewei; Ting, Ye; Li, Shengkang; Ma, Hongyu; Zheng, Huaiping (Frontiers in Microbiology, 2020)
Many marine bivalves are regarded as healthy foods due to their high carotenoids content. Only plants and microorganisms have natural carotenoids biosynthesis ability, Due to the filter-feeding behavior of bivalves, they have high diversity of gut microbes. However, the relationship between gut microbes and carotenoids has not been explored in mollusks. In the present study, the interaction between gut microbes and carotenoids in two polymorphic noble scallop Chlamys nobilis, golden scallops (designated GG) and brown scallops (designated BW) were studied. The gut of GG and BW showed statistically different bacteria communities. Results from 16S rRNA gene sequencing and qPCR analysis revealed that the gut of GG had significantly higher relative abundance of carotenoids-producing bacteria Brevundimonas, compared with BW. Moreover, HPLC-MS analysis showed that isolate Brevundimonas could produce astaxanthin. The current findings are very useful as they could form the basis for future studies in determining the relationship between gut microbiota and carotenoids absorption in bivalves.